PENGARUH SUPERVISI AKADEMIK DAN KEPUASAN KERJA GURU TERHADAP PROFESIONALISME GURU SEKOLAH DASAR NEGERI DI KECAMATAN KEMBANG KABUPATEN JEPARA - Dyan Retno Murtining Tyas; Noor Miyono; Widya Kusumaningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The success of teacher professionalism is largely determined by the success of the principal in managing the teaching and educational staff in the school. The school principal is one component of education that has an influence in increasing teacher professionalism. The school principal is responsible for organizing educational activities, school administration, developing teaching staff, utilizing and maintaining facilities and infrastructure. The aims of this research are (1) to determine the influence of academic superstition on teacher professionalism (2) to determine the influence of job satisfaction on teacher professionalism (3) to determine the influence of academic supervision and job satisfaction together on teacher professionalism of elementary school teachers in Kembang District, Jepara Regency. The population of this study were teachers at 42 elementary schools in Kembang District, Jepara Regency, totaling 310 people, a sample of 175 teachers selected using proportional random sampling technique at each school. Validity, reliability and descriptive data analysis tests, single regression and multiple regression tests using the SPSS for Windows version 23 program. Research findings: (1) the influence of academic supersition on teacher professionalism is 14.4% with the regression equation Ŷ = 70,987 + 0.328 X2. (3) the influence of academic supervision and job satisfaction together on on teacher professionalism is 22% with the regression equation Ŷ = 42.655 + 0.206X1 + 0.403X2, Based on the findings above: (1) the principal intensifies the evaluation of supervision results, (2) the principal increases supervision in the main work tasks of teachers, (3) teachers increase involvement in school activities.